The Role Of Multi-Helix Collaboration In Education Improvement In Special Autonomous Regions: A Systematic Literature Review (International Journal of Environmental Sciences, 2025)
Background: Multi-helix collaboration models have emerged as critical frameworks for education policy development and implementation, particularly in special autonomous regions where complex governance structures require coordinated stakeholder engagement.Objective: This systematic literature review examines the effectiveness of multi-helix collaboration in improving educational access, quality, and equity in special autonomous regions, identifying key success factors and stakeholder contributions.Methods: Following PRISMA guidelines, we conducted a comprehensive search across ProQuest, ScienceDirect, Lens, and EmeraldInsight databases from January 2014 to December 2024. Search terms included combinations of 'Multi-Helix,' 'Collaborative Governance,' 'Education,' 'Educational Quality,' 'Regional Autonomy,' and 'Self-Governance.' After systematic screening, 24 high-quality articles were selected for thematic analysis and bibliometric examination using VOSviewer.Results: Four critical success factors emerged: (1) clear and adaptive regulatory frameworks, (2) facilitative leadership, (3) adequate digital infrastructure, and (4) meaningful local community engagement. Primary barriers included institutional capacity gaps, infrastructure limitations, stakeholder conflicts, and low inter-actor trust. Government contributions focused on policy formulation and resource allocation; academia provided research and capacity building; industry offered practical skills training and employment linkages; civil society ensured accountability and community mobilization; media facilitated public discourse and transparency.Conclusions: Multi-helix collaboration shows significant potential for educational transformation in special autonomous regions when enabling conditions are met. Success requires systematic address of capacity gaps, infrastructure development, trust-building mechanisms, and sustained stakeholder commitment. The framework's effectiveness depends on contextual adaptation and continuous organizational learning processes.